Hum : Stories - Richmond, Michelle, 1970- (Book collections on Project MUSE., 2014)
A new collection of stories by bestselling author Michelle Richmond, Hum presents a cautionary political fable, a celebration of the complexities of marriage, and a meditation on modern-day alienation. Thirteen years after the publication of her first story collection, The Girl in the Fall-Away Dress, New York Times bestselling author Michelle Richmond returns with Hum, a collection of ten stories that examine love, lust, and loyalty from surprising angles. In "Hum," a young couple that is paid to live in a house filled with surveillance equipment become